Sign Language Communication Method an Identity in Deaf Community and Culture for Human Development (FULAFIA IAC Book of Proceedings, 2024)
The paper looked at sign language as a manual system of communication commonly used by persons with hearing impairment. It is expressed through manual system using hand gestures and movement, body language and facial expressions instead of spoken words when the spoken words become impossible, not desirable or becomes difficult at stuttering. Sign Language is not universal as people who are deaf in different countries use different sign languages. It has it’s own distinct parts of hand shape, palm orientation, movement and location to create signs. Communications is the imparting or exchanging of information and knowledge by speaking, writing or the use of other medium like sign language and finger spelling. The paper went further to tease out deaf community as a group of people with similar medical problem which is hearing impairment or hearing loss or deafness, but also include their family members and sign language interpreters and view hearing impairment as a difference in human expression rather than a disability or disease. The paper again see deaf culture as a way of life, a set of social beliefs, behaviours, arts, traditions, history, value and shared institution of community that is influenced by deafness and which use sign language as their identity and main means of communication. The paper is concluded with the recommendations that the hearing world should encourage inclusivity with the deaf world. Treat them like fellow human beings in socio-economic development.